Characterization of biodegradable composite based on polycaprolactone/starch reinforced with sugarcane bagasse microfibrillated cellulose - Jimat, Dzun Noraini; Ariffin, Faridah; Asem, Maimunah; Sulaiman, Sarina (Akademia Baru, 2017)
Biodegradable polymers have been extensively studied in order to substitute the synthetic polymers since they are non-biodegradable which is harmful to environment. Polycaprolactone (PCL) could be a good candidate to substitute synthetic polymer since it can be slowly degraded by microbes. PCL was synthesized by ring-opening polymerization of -caprolactone with stannous octoate as catalyst. To improve the mechanical strength of PCL, it was reinforced with microfibrillated cellulose (MFC) and starch acts as filler. MFC was extracted from sugarcane bagasse (SCB) through chemo-mechanical treatments. Characterizations of the PCL-starch composite reinforced with MFC-SCB with respect to its morphology and structural changes as well as its thermal degradation were evaluated. In this study, amount of tapioca starch was fixed at 40%. Meanwhile, the composition of PCL and MFC-SCB were varied from 50% to 58% and 2% to 10% respectively. Initial observation from microscopy images showed that there were significant changes of morphology of PCL after adding starch and SCB-MFC. As shown in SEM images, the surface of biocomposite PCL-starch-MFC-SCB was quite uniform and smooth with less 5% of MFC-SCB. However, fine aggregates were observed on the sample with 10% of MFC-SCB due to the presence of sugarcane bagasse microfibril cellulose.